qanda-logo
search-icon
Símbolos
Problema
solution-image
Operación Simplificación a) $\right)$ $\left(5ax^{2}\right)\left(a^{2}x^{3}$ $\right)\left(6ax\right)=$ $b\right)$ $\left(9a^{3}b^{4}c\right)^{2}.\left(2a^{2}b^{3}\right)^{3}.\left(ac\right)=$ $\right)$ $\left(\dfrac {2} {b^{2}}\right)^{3}$ $.\left(\dfrac {b^{3}} {4}\right)^{2}.\left(\dfrac {1} {b^{2}}\right)^{2}=$ d) $\dfrac {\left(-2m^{2}n^{5}\right)^{4}} {\left(12m^{3}n^{5}\right)^{3}}=$ $\bar{9} $ $\left(\dfrac {2p} {3q^{2}r^{3}}\longdiv{}3.\left(\dfrac {p^{3}r^{2}} {9^{4}}\right)^{2}=$ $7\dfrac {9^{3n}y^{m+4}} {9^{2n}y^{m}}=$
Secundaria
Aritmética y álgebra
Búsquedas: 129
Solución
answer-user-profile-image
Profesor de Qanda - Pavel
answer-reply-image
answer-reply-image